An empirically based simulation model to inform flow management for endangered species conservation - Walsworth, Timothy E; Budy, Phaedra (Canadian journal of fisheries and aquatic sciences, 2021)
Increasing water demand, water development, and ongoing climate change have driven extensive changes to the hydrology, geomorphology and biology of arid-land rivers globally, driving an increasing need to understand how annual hydrologic conditions affect the distribution and abundance of imperiled desert fish populations. We analyzed the relationship between annual hydrologic conditions and the endangered Rio Grande silvery minnow (Hybognathus amarus) in the Middle Rio Grande, New Mexico, USA, using hurdle models to predict both presence and density as a function of integrated annual hydrologic metrics. Both presence and density were positively related to spring high flow magnitude and duration and negatively related to summer drying, as indicated by an integrated flow metric. Simulations suggest hydrologic conditions near the wettest observed in the data set would be required to meet recovery goals in a single year in all reaches. We demonstrate how the models developed herein can be used to examine alternative water management strategies, including strategies that may currently be socially and logistically infeasible to implement, to identify strategies minimizing trade-offs between conservation and other management goals.